Prevalensi dan Dampak Kecanduan Gadget Pada Remaja: Literature Review - Mentari Kusuma Rini; Titih Huriah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To know the prevalence and impact of gadgets addiction on youth. Method: The method utilized in this paper was a literature review of international journals conducted using the PubMed, ProQuest, Goggle Scholar database. At the initial stage of the search with the keywords: "((prevalence AND impact AND smartphone addiction OR internet addiction] AND adolescent))" it gained 14 international articles from the range of 2016 to 2018 which were in accordance with the inclusion and exclusion criteria.Results: From the 14 articles, there were 6 articles that discussed the prevalence of internet addiction 2 of which occurred in developed countries such as Japan and Taiwan, from the two countries the prevalence of internet addiction was 22.6% on average. Meanwhile, the prevalence in developing countries such as Turkey, Tunisia, China and India averaged 32.3%. Eight articles reviewed the effects of internet addiction. The impacts of using gadgets can beÂ  seen physically (Obesity) and psychologically [Depression, loneliness, suicide, sleep disturbance, attention deficit disorder and hyperactivity] and other impacts such as family dysfunction.Conclusion: The review of this literature review has gained the different prevalence of gadget and internet addiction between developed and developing countries in which the developed countries was 22.6% while developing countries was 32.3%. The impacts given of this addiction were the physical, psychological and family function impacts.Â Keywords: Gadgets, Internet, Addiction, Youth